Clinical Factors Influencing End-of-Life Care in a Chinese Pediatric Intensive Care Unit: A Retrospective, post-hoc Study - Zhu, Yueniu; Zhu, Xiaodong; Xu, Lili; Deng, Mengyan (Frontiers in Pediatrics, 2021)
Objective: End-of-life care decision-making for infants and children is a painful experience. The study aimed to explore the factors influencing the decision to withhold/withdraw life-sustaining treatment (WLST) in Chinese pediatric intensive care unit (PICU). Methods: A 14-year retrospective study (2006-2019) for pediatric patients who died in PICU was conducted. Based on the mode of death, patients were classified into WLST group (death after WLST) and fCPR group (death after full intervention, including cardiopulmonary resuscitation). Intergroup differences in the epidemiological and clinical factors were determined. Results: There were 715 patients enrolled in this study. Of these patients, 442 (61.8%) died after WLST and 273 (38.2%) died after fCPR. Patients with previous hospitalizations or those who had been transferred from other hospitals more frequently chose WLST than fCPR (both P < 0.01), and the mean PICU stay duration was significantly longer in the WLST group (P < 0.01). WLST patients were more frequently complicated with chronic underlying disease, especially tumor (P < 0.01). Sepsis, diarrhea, and cardiac attack (all P < 0.05) were more frequent causes of death in the fCPR group, whereas tumor as a direct cause of death was more frequently seen in the WLST group. Logistic regression analysis demonstrated that previous hospitalization and underlying diseases diagnosed before admission were strongly associated with EOL care with WLST decision (OR: 1.6; P < 0.05 and OR: 1.6; P < 0.01 respectively). Conclusions: Pediatric patients with previous hospitalization and underlying diseases diagnosed before admission were associated with the decision to WLST.